Sistem Informasi Jasa Sewa Jas dan Blazer Berbasis Web - Nurul Khofifah Siregar; Boni Oktaviani Sembiring; Dedy Irwan (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
The formal clothing rental industry such as suits and blazers has had significant growth potential in recent years. The demand for formal wear for various occasions such as weddings, parties and business events is increasing. Suit and blazer rental service providers still manage their business conventionally, using manual records in managing clothing inventory, orders and payments. This method is less effective, the development of a web-based information system for jacket and blazer rental services is very important. This information system will provide an effective solution for managing clothing inventory, placing orders online, facilitating the payment process, and providing accurate and up-to-date information to service providers and customers.